Nutritional Status of Pre-School Children Attending Anganwadi Centres in Chittoor, Andhra Pradesh, India - Sravana Deepthi C; Erigela Mallikarjuna Reddy; Sirshendu Chaudhuri; Rizwana Syed (Medsci Publications, 2022)
Context/Background: Malnutrition among children is a long-standing public health problem in India. Objective: To assess the nutritional status of pre-school children and to identify the socio-demographic determinants of malnutrition. Methodology: In this community-based cross-sectional study, 194 under-five children were recruited from rural and urban areas of Chittoor district, Andhra Pradesh. Anthropometric measurements including weight, and mid upper arm circumference were measured and age standardized weight-for-age (WAZ), height-for-age (HAZ), and weight-for-height (WHZ) were calculated. The proportion of under nutrition (WAZ <-2 standard deviation (SD)), stunting (HAZ <-2SD), and wasting (WHZ <-2SD) were calculated along with the determinants. Results: The mean age of the participants was 40.5 months (SD- 9.1 months), 101 (52.1%) were from rural areas, and 96 (495%) female. The median z-scores for WAZ, HAZ, and WHZ were -1.22, -0.98, and -0.78respectively. The HAZ values were significantly low in- urban children (-0.81; 95% CI: -0.4, -1.21), among the non-Hindu children (-0.92; 95% CI: -0.35, -1.5). The overall prevalence of underweight, stunting, and wasting were- 13.4% (95% CI: 8.5%, 18.3%), 23.7% (95% CI: 17.6%, 29.8%), and 19.6% (95% CI: 11.9%, 25.3%) respectively. There were a total 16 (8.3%, 95% CI: 5.6%, 11.0%) severely malnourished children. Urban residence (OR 6.75; 95% CI: 3.03 - 15.04) was a strong predictor of stunting. Conclusion: Malnutrition remains to be a public health problem in this area. Strengthening of existing program implementation coupled with evidence generation on malnutrition can be the key strategies in combating malnutrition.